2020
DOI: 10.1158/2159-8290.cd-20-0387
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis and Immune Evasion from Extracellular cGAMP Hydrolysis

Abstract: Cytosolic DNA is characteristic of chromosomally unstable metastatic cancer cells, resulting in constitutive activation of the cGAS–STING innate immune pathway. How tumors co-opt inflammatory signaling while evading immune surveillance remains unknown. Here, we show that the ectonucleotidase ENPP1 promotes metastasis by selectively degrading extracellular cGAMP, an immune-stimulatory metabolite whose breakdown products include the immune suppressor adenosine. ENPP1 loss suppresses metastasis, restores tumor im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
173
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(178 citation statements)
references
References 50 publications
3
173
1
1
Order By: Relevance
“…Here, we will briefly discuss recent findings that emphasize the role of the cGAS-STING pathway in restricting the anti-tumoral immune response and favoring evasion from immune control. Recently, Li and colleagues demonstrated that the ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) promotes metastasis by degrading cGAMP and contributing to the production of adenosine (an immune-suppressive and tumor-promoting metabolite) [ 156 ]. In human cancers, the expression of ENPP1 correlates with lower immune infiltration and resistance to CPIs [ 156 ].…”
Section: Non-genetic Mechanisms Of Immune Evasion In Microsatellite Unstable Crcmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we will briefly discuss recent findings that emphasize the role of the cGAS-STING pathway in restricting the anti-tumoral immune response and favoring evasion from immune control. Recently, Li and colleagues demonstrated that the ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) promotes metastasis by degrading cGAMP and contributing to the production of adenosine (an immune-suppressive and tumor-promoting metabolite) [ 156 ]. In human cancers, the expression of ENPP1 correlates with lower immune infiltration and resistance to CPIs [ 156 ].…”
Section: Non-genetic Mechanisms Of Immune Evasion In Microsatellite Unstable Crcmentioning
confidence: 99%
“…Recently, Li and colleagues demonstrated that the ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) promotes metastasis by degrading cGAMP and contributing to the production of adenosine (an immune-suppressive and tumor-promoting metabolite) [ 156 ]. In human cancers, the expression of ENPP1 correlates with lower immune infiltration and resistance to CPIs [ 156 ]. Additional findings confirm that the cGAS-STING pathway may regulate the immunogenicity of cancer cells.…”
Section: Non-genetic Mechanisms Of Immune Evasion In Microsatellite Unstable Crcmentioning
confidence: 99%
“…However, the immune-activating potential of PARPi may be context-dependent. For example, tumor cells that express the ectonucleotidase ENPP1 degrade extracellular cGAMP, whose breakdown products can be further metabolized to adenosine, an immunosuppressive metabolite, toggling the cGAS-STING pathway from immunostimulatory to immunosuppressive [ 120 ]. Furthermore, PARPi treatment is associated with upregulation of the checkpoint molecule programmed death ligand 1 (PD-L1) [ 121 ].…”
Section: Tumor Intrinsic and Extrinsic Determinants Of Hrdmentioning
confidence: 99%
“…Prior reports have revealed that recruitment of cGAS to cytosolic DNA generate cGAS foci 18,19 . Since cGAS-STING-dependent interferon-stimulated genes (ISG) induction following DNA damage was restricted largely to cardiac fibroblasts, we next examined (which was not certified by peer review) is the author/funder.…”
Section: Main Textmentioning
confidence: 99%